Preparation, Characterization, and Cytoprotective Effects on HUVECs of Fourteen Novel Angiotensin-I-Converting Enzyme Inhibitory Peptides From Protein Hydrolysate of Tuna Processing By-Products - Qiao, Qian-Qian; Luo, Qian-Bin; Suo, Shi-Kun; Zhao, Yu-Qin; Chi, Chang-Feng; Wang, Bin (Frontiers in Nutrition, 2022)
To effectively utilize skipjack tuna (Katsuwonus pelamis) processing by-products to prepare peptides with high angiotensin-I-converting enzyme (ACE) inhibitory (ACEi) activity, Neutrase was selected from five kinds of protease for hydrolyzing skipjack tuna dark muscle, and its best hydrolysis conditions were optimized as enzyme dose of 1.6%, pH 6.7, and temperature of 50°C using single factor and response surface experiments. Subsequently, 14 novel ACEi peptides were prepared from the high ACEi protein hydrolysate and identified as TE, AG, MWN, MEKS, VK, MQR, MKKS, VKRT, IPK, YNY, LPRS, FEK, IRR, and WERGE. MWN, MEKS, MKKS, and LPRS displayed significantly ACEi activity with IC50 values of 0.328 ± 0.035, 0.527 ± 0.030, 0.269 ± 0.006, and 0.495 ± 0.024 mg/mL, respectively. Furthermore, LPRS showed the highest increasing ability on nitric oxide (NO) production among four ACEi peptides combining the direct increase and reversing the negative influence of norepinephrine (NE), and MKKS showed the highest ability on directly decreasing and reversing the side effects of NE on the secretion level of endothelin-1 (ET-1) among four ACEi peptides. These findings demonstrate that seafood by-product proteins are potential ACEi peptide sources and prepared ACEi peptides from skipjack tuna dark muscle, which are beneficial components for functional food against hypertension and cardiovascular diseases.